THU0330 EFFECTS OF NINTEDANIB IN PATIENTS WITH SYSTEMIC SCLEROSIS-ASSOCIATED ILD (SSC-ILD) AND DIFFERING EXTENTS OF SKIN FIBROSIS: FURTHER ANALYSES OF THE SENSCIS TRIAL. (2nd June 2020) - Allanore, Y.; Steen, V.; Kuwana, M.; Denton, C.; Matucci-Cerinic, M.; Volkmann, E.; Khanna, D.; Wachtlin, D.; Gahlemann, M.; Quaresma, M.; Alves, M.; Distler, O.
Abstract : Background: In the SENSCIS trial, nintedanib reduced the progression of SSc-ILD compared with placebo, as shown by a significantly lower rate of decline in forced vital capacity (FVC) over 52 weeks. There was no significant difference between treatment groups in change in modified Rodnan skin score (mRSS) at week 52. An mRSS of 18–25 has been proposed as an upper cut-off to enrich a cohort for skin-progressive patients. Progression of skin fibrosis has been associated with later progression of ILD. Objectives: To assess the effects of nintedanib on the rate of FVC decline and change in mRSS in the SENSCIS trial in subgroups by mRSS <18 and ≥18 at baseline. Methods: Patients with SSc-ILD with onset of first non-Raynaud symptom <7 years before screening and ≥10% fibrosis of the lungs on a high-resolution computed tomography scan were randomised to receive nintedanib or placebo. We analysed the rate of decline in FVC (ml/year) over 52 weeks and the change from baseline in mRSS at week 52 in subgroups by mRSS (<18; ≥18) at baseline. Results: In the nintedanib and placebo groups, respectively, 219/288 (76.0%) and 226/288 (78.5%) patients had mRSS <18 at baseline. Compared with those with mRSS <18, patients with mRSS ≥18 had a lower mean FVC % predicted (68.3% vs 73.7%) and greater proportions were taking mycophenolate at baseline (58.1% vs 45.6%), were anti-topoisomerase I antibody positive (67.4% vs 58.7%) and had diffuse cutaneous SSc (100% vs 37.8%). The mean (SE) annual rate of decline in FVC in the placebo group was numerically greater in patients who had mRSS ≥18 than mRSS <18 at baseline (-131.7 [29.2] mL/year vs -81.4 [15.4] mL/year). The effect of nintedanib vs placebo on reducing the annual rate of decline in FVC was numerically more pronounced in patients with mRSS ≥18 (difference: 88.7 mL/year [95% CI 7.7, 169.8]) than mRSS <18 (difference: 26.4 mL/year (95% CI -16.8, 69.6) at baseline, but statistical testing did not indicate heterogeneity in the treatment effect of nintedanib between subgroups (p=0.18 for treatment-by-time-by-subgroup interaction) (Figure). In the nintedanib and placebo groups, respectively, changes in mRSS at week 52 were -2.2 (0.3) and -2.1 (0.3) (difference -0.1 [95% CI -1.0, 0.7]) in patients with mRSS <18 at baseline and -2.1 (0.7) and -1.6 (0.7) (difference -0.6 [95% CI -2.1, 1.0]) in patients with mRSS ≥18 at baseline (p=0.62 for treatment-by-visit-by-subgroup interaction). Conclusion: In the placebo group of the SENSCIS trial, the rate of decline in FVC over 52 weeks was numerically greater in patients with mRSS ≥18 than <18 at baseline, while reductions in mRSS were similar. A lower rate of FVC decline was observed in patients treated with nintedanib than placebo both in patients with mRSS ≥18 and <18 at baseline. Acknowledgments: The SENSCIS trial was funded by Boehringer Ingelheim Disclosure of Interests: Yannick Allanore Grant/research support from: Yannick Allanore has received grants from Inventiva, Roche and Sanofi, Consultant of: Yannick Allanore has received fees from Actelion, Bayer, Boehringer Ingelheim, Bristol-Myers Squibb, Curzion, Inventiva, Roche, Sanofi, Viginia Steen Grant/research support from: The associated affiliation has received grants/research from Boehringer Ingelheim, Corbus Pharmaceuticals, CSL Behring, Eicos, Galapagos, Immune Tolerance Network, Reata, Consultant of: Virginia Steen has acted as a consultant for Boehringer Ingelheim, Corbus, CSL Behring, Eicos, Forbius, Masataka Kuwana Grant/research support from: Acetelion, Consultant of: Acetelion, Bayer, Chugai, Corbus Pharmaceuticals, CSL Behring and Reata Pharmaceuticals. He was a member of the SENSCIS trial Steering Committee (Boehringer Ingelheim), Christopher Denton Grant/research support from: GlaxoSmithKline, CSL Behring, and Inventiva, Consultant of: Medscape, Roche-Genentech, Actelion, GlaxoSmithKline, Sanofi Aventis, Inventiva, CSL Behring, Boehringer Ingelheim, Corbus Pharmaceuticals, Acceleron, Curzion and Bayer, Marco Matucci-Cerinic Grant/research support from: Actelion, MSD, Bristol-Myers Squibb, Speakers bureau: Acetelion, Lilly, Boehringer Ingelheim, Elizabeth Volkmann Grant/research support from: Forbius, Corbus Pharmaceuticals, Consultant of: Boehringer Ingelheim, Forbius, Speakers bureau: Boehringer Ingelheim, Dinesh Khanna Shareholder of: Eicos Sciences, Inc./Civi Biopharma, Inc., Grant/research support from: Dr Khanna was supported by NIH/NIAMS K24AR063120, Consultant of: Acceleron, Actelion, Bayer, Boehringer Ingelheim, Bristol-Myers Squibb, Corbus Pharmaceuticals, Horizon Therapeutic, Galapagos, Roche/Genentech, GlaxoSmithKline, Mitsubishi Tanabe, Sanofi-Aventis/Genzyme, UCB, Daniel Wachtlin Employee of: Employee of Boehringer Ingelheim, Martina Gahlemann Employee of: Employee of Boehringer Ingelheim, Manuel Quaresma Employee of: Employee of Boehringer Ingelheim, Margarida Alves Employee of: Employee of Boehringer Ingelheim, Oliver Distler Grant/research support from: Grants/Research support from Actelion, Bayer, Boehringer Ingelheim, Competitive Drug Development International Ltd. and Mitsubishi Tanabe; he also holds the issued Patent on mir-29 for the treatment of systemic sclerosis (US8247389, EP2331143)., Consultant of: Consultancy fees from Actelion, Acceleron Pharma, AnaMar, Bayer, Baecon Discovery, Blade Therapeutics, Boehringer, CSL Behring, Catenion, ChemomAb, Curzion Pharmaceuticals, Ergonex, Galapagos NV, GSK, Glenmark Pharmaceuticals, Inventiva, Italfarmaco, iQvia, medac, Medscape, Mitsubishi Tanabe Pharma, MSD, Roche, Sanofi and UCB, Speakers bureau: Speaker fees from Actelion, Bayer, Boehringer Ingelheim, Medscape, Pfizer and Roche